Assessment strategies for knowledge organizations - Testa, Dean; Brown-Grant, Johel; Bedford, Denise (Working methods for knowledge management, 2019)
As organizations transform from an industrial to knowledge-based economy, assessment strategies are rarely adapted to the new environment. Offering an enhanced understanding of how to engage organisations in assessments, this is an unmissable book for knowledge management professionals and researchers.